Strategi Pengelolaan Pasar Aman Di Balai Besar Pengawasan Obat Dan Makanan Kota Makassar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine the strategy of safe market management in the large halldrug and food supervision in Makassar city. This study used qualitative. The number of informants in this st udy were 5 people. Data collection used observation, interviews with a number of informants. The data analysis technique used  interactive analysis. The results of this study indicated that the determination of the Head of UPTD Market as program director had been effective in the implementation of the safe market in Makassar City, its centralized system bused in the implementation of a market strategy of safe from hazardous substances had been effective and brings good impact, the job specifications of each sub-unit were determined by the program director and great hall  POM Makassar City had been effective. Plans, programs and budgets were carried out by each sub-work unit based on the guidelines for implementing the safe market had been effective and accordance with the needs and circumstances field, job descriptions on the safe market strategy compiled by each sub unit had been effective,The implementation of routine work in the safe market program was still not maximal, marked by a process advocacy programs to the Makassar City Government did not involve the community and the University, the period of sampling and testing was still minimal, guidance on individual traders needed to be improved.Keywords: management strategy, market, safe,